Effect of Shape and Size of Purple Nutsedge (Cyperus rotundus L.) Tuber Bioherbicide Granules on the Germination of Weed and Crop Seeds - Sahara, Olyvia Fashatus; Chozin, Muhamad Achmad; Hapsari, Dhika Prita (Department of Agronomy and Horticulture, IPB University, 2026)
The use of synthetic herbicides is an effective way to control weeds, but their widespread use has negative environmental impacts. A bioherbicide made from purple nutsedge tubers can be an alternative for weed control. Purple nutsedge’s tuber contain allelopathy compounds that can inhibit the growth of other plants (weeds). This study aims to evaluate the response of various shapes and sizes of bioherbicide granules made from purple nutsedge’s tuber in suppressing the germination of weed seeds and crop seeds. The experiment used a completely randomized design one factor and eleven treatments: control without herbicide treatment, synthetic herbicide active ingredient oxyfluorfen 240 g/L, purple nutsedge’s tuber powder bioherbicide without carrier, very small round granule bioherbicide, small round granule, medium round granule, large round granule, very small cylindrical granule, small cylindrical granule, medium cylindrical granule, and large cylindrical granule. Each treatment was tested on four species: Bidens pilosa and Cynodon dactylon (weeds), cucumber, and rice (crops). The experimental results showed that the application of purple nutsedge’s tuber-based bioherbicides exerts a noticeable influence on several germination parameters. The smaller the bioherbicide granule, the higher the germination inhibition rate. Very small, round-shaped granule bioherbicides showed greater effectiveness in suppressing seed sprout percentage, reducing growth rate, increasing the percentage of abnormal sprouts, and inhibiting plumula and radicle growth.